Zgodnja medicinska rehabilitacija v bolnišnicah - izkušnje specialistov fizikalne in rehabilitacijske medicine Inštituta za medicinsko rehabilitacijo UKC Ljubljana - Kos, Nataša (Rehabilitacija (Ljubljana), 2015)
We describe the importance of acute rehabilitation in a hospital setting. The problems connected with performing different rehabilitative procedures in a hospital room are addressed, as well as the difficulties faced when discharging patients who are not yet capable to return safely to their domestic environment.
Keywords: acute rehabilitation; bolnišnice; Hospitals; interdisciplinarni tim; interdisciplinary team; rehabilitacijski postopki; Rehabilitation; rehabilitative procedures; zgodnja rehabilitacija